GLOBAL WARMING. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the problem of global warming, its causes, and its impact on human life. The increase in greenhouse gas emissions, climate changes, melting of polar ice caps, and rising sea levels are considered the main consequences of global warming. The article also analyzes proposed measures to maintain ecological balance and prevent global warming. The topic aims to foster environmental awareness among readers and promote understanding of sustainable development methods.